The Importance of Enhancing Professional Excellence in Higher Education for Ensuring State Security - V. V. ZASANSKYI; A. M. SOROKA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article raises the issue of the importance of ensuring high-quality training of specialists in higher education based on the use of the latest teaching methods and their importance for ensuring the economic security of the state as the main foundation of national security. It is not for nothing that they say that personnel decide everything. The importance of combining advanced practice and the latest creative pedagogical thought is noted. A model of a comprehensive approach to teaching in higher education is proposed. Integration of classical assessment methods with the latest trends. In particular, holding interactive round tables. Using modern educational components of various technical platforms, in particular such as zoom and meet. Google. These platforms make it possible to use lectures by the best scientists in the world in the educational process. It is proven that such a comprehensive approach contributes to the development of training of highly qualified personnel for all sectors of the economy and the military-industrial sector, departmental universities of the Ministry of Internal Affairs, the Ministry of Defense of Ukraine. High-quality training of specialists is the basis for the formation of National Security.